Critical analysis of cell block versus smear examination in effusions - Thapar Meenu; Mishra Rajiv; Sharma Amit; Goyal Vikas; Goyal Vibhuti (Journal of Cytology, 2009)
Objectives: To assess the utility of the cell block preparation method in increasing the sensitivity of cytodiagnosis of serous fluids and to know the primary site of malignant effusions. Materials and Methods: A total of 190 cases were subjected to routine smear examination as well as cell block preparation. After the cytological diagnosis, each case was objectively analysed for cellularity, arrangement (acini, papillae, cell balls, and proliferation spheres), cytoplasmic, and nuclear details. Results: Out of 190 cases, 70 cases were found to be malignant and had been examined in smears and paraffin-embedded cell blocks. Using a combination of the cell block and smear techniques yielded 13% more malignant cases than what were detected using smears by themselves. The combined technique helped to ascertain the primary site of malignancy in 83.3% of the cases, whereas the primary site could not be ascertained in 17.7% of the cases. Conclusions: The cell block technique not only increased the positive results, but also helped to demonstrate better architectural patterns, which could be of great help in making correct diagnosis of the primary site. The cell block technique was also useful for special stains and immunohistochemistry and can give morphological details by preserving the architectural patterns.